POLITICAL AND LEGAL ANALYSIS IN PUBLIC INFORMATION DISCLOSURE FROM A GOOD GOVERNANCE PERSPECTIVE IN INDONESIA - Putu Gita Sunia Sari; Ni Made Anggia Paramesthi Fajar; Ni Ketut Sari Adnyani (Awang Long Law Review, 2026)
Public information disclosure is a fundamental element in democratic governance based on the principles of good governance. Law Number 14 of 2008 concerning Public Information Disclosure was formed to shift the government's political culture from a pattern of secrecy to openness. However, in its implementation, this law still faces challenges related to the political configuration of the law and bureaucratic resistance. This study examines the politics of law in the implementation of the Public Information Disclosure Law and assesses its effectiveness in encouraging a culture of openness. This research uses a normative juridical method with a legislative, conceptual, and case approach through a literature study of laws and regulations, information dispute decisions, and relevant scientific literature. The results of the study show that the legal politics of public information disclosure are ambivalent. On the one hand, the laws and decisions of the Information Commission have expanded public access to information, but on the other hand, implementing regulations and internal bureaucratic policies are still often used to maintain a culture of secrecy. This study concludes that the effectiveness of the law in encouraging openness is still limited and is greatly influenced by the power relations between the state, the bureaucracy, and society.